Hyperhomocysteinemia and low vitamin B12 associated with autonomic dysfunction in Parkinson’s disease: A time domain analysis of heart rate variability - Akther, Rubina; Sultana, Shamima; Nova, Naoreen Khan; Habib, Ahsan (Journal of Bangladesh Society of Physiologist, 2024)
Background: Parkinson’s disease (PD) is associated with autonomic dysfunction as well as hyperhomocysteinemiaand low serum vitamin B12 level. Heart rate variability (HRV) is an important tool for assessing autonomic function.Objective:To evaluate the association of  hyperhomocysteinemia and low vitamin B12with autonomic dysfunction by time domain measures of HRV in male patients with PD. Methods: This observational analytical cross sectional study was conducted on 30 newly diagnosed male PD patients of 50-60 years age attending Out Patient Department of the Department of Neurology, BSMMU, Dhaka. Thirty (30) age and BMI matched apparently healthy male subjects were included as control for comparison. Serum vitamin B12 and homocysteine were measured by chemiluminescent immunoassay method and HRV were measured by time domainmethod using a data acquisition device, Powerlab 8/35, AD instruments. Independent sample t-test and Pearson’s correlation coefficient test were used for statistical analysis by SPSS version 25 and p value <0.05 were considered as statistical significance.  Results: In this study, resting pulse rate and mean heart ratewere found significantly higher (p<0.001) and mean RR interval, standard deviation of the RR intervals (SDRR), coefficient variation of RR interval (CVRR), standard deviation of the difference between successive RR intervals (SDSD), square root of mean squared differences of successive RR intervals (RMSSD), proportion of RR interval with duration >50ms (pRR50%)were found significantly lower (p<0.001) in PD patients  compared to control. In addition, serum vitamin B12 level was found significantly lower (p<0.01) and homocysteine level was found significantly higher (p<0.001) in PD patients than that of control. On correlation analysis, serum homocysteine was significantly negatively correlated with SDSD (p<0.01) and RMSSD (p<0.01). Conclusion:Hyperhomocysteinemiais associated with autonomic dysfunction in male patients with PD. J Bangladesh Soc Physiol 2023;18(1): 1-8